Serum albumin-adjusted glycated albumin is a better indicator of glycaemic control in diabetic patients with end-stage renal disease not on haemodialysis. (July 2015) - Fukami, Kei; Shibata, Ryo; Nakayama, Hitomi; Yamada, Kentaro; Okuda, Seiya; Koga, Masafumi
Backgrounds: Diabetic patients with end-stage renal disease who are not on haemodialysis show low concentrations of HbA1c and glycated albumin due to renal anaemia and proteinuria, respectively. In the present study, we examined whether serum albumin-adjusted glycated albumin could accurately reflect glycaemic control in these patients. Methods: To examine the correlation between glycated albumin and serum albumin (Study 1), 49 diabetic patients with end-stage renal disease not on haemodialysis were used. To evaluate the association between the glycaemic control indicators and the glycaemic control state (Study 2), 30 diabetic patients with end-stage renal disease were enrolled. The estimated HbA1c and the estimated glycated albumin concentrations were calculated based on the mean blood glucose concentrations obtained from the diurnal variation. The adjusted glycated albumin concentrations were calculated from the regression formula between the serum albumin and glycated albumin obtained from Study 1. Results: No significant correlation was found between the measured HbA1c and estimated HbA1c concentrations. The estimated HbA1c (inversely) and measured HbA1c/estimated HbA1c ratio (positively), but not measured HbA1c, showed a significant correlation with Hb concentrations. The estimated glycated albumin was positively associated with the measured glycated albumin and adjusted glycated albumin concentrations. Although measured glycated albumin/estimated glycated albumin ratio was positively correlated with serum albumin, there was no significant association between the adjusted glycated albumin/estimated glycated albumin ratio and serum albumin, Hb and estimated glomerular filtration rate. Conclusions: We found for the first time that the adjustment of glycated albumin by serum albumin could be useful to determine glycaemic control in diabetic patients with end-stage renal disease not on haemodialysis. These findings suggest that adjusted glycated albumin might be a better indicator of glycaemic control than measured HbA1c and measured glycated albumin in these patients.